Current characteristics of hemophilia patients co-infected with HIV/HCV in Japan - Miuma, Satoshi (Exp Ther Med, 2018)
Over 30 years have passed since co-infection with human immunodeficiency virus (HIV)/hepatitis C virus (HCV) was first documented in hemophilia patients in Japan. In such cases, the leading cause of mortality is reportedly HCV-associated end-stage liver disease. However, the current characteristics of hemophilia patients co-infected with HIV/HCV are unknown. The aim of the present study was to reveal the current characteristics, notably HCV geno-prevalence and liver function, among hemophilia patients co-infected with HIV/HCV in Japan. Current characteristics were evaluated using cross-sectional retrospective data of 44 hemophilia patients positive for anti-HCV and anti-HIV antibodies who underwent screening of liver dysfunction. A total of 56.8% of hemophilia patients co-infected with HIV/HCV were positive for HCV RNA. The most common HCV genotypes were 1a, 1b and 3a. Liver cirrhosis was diagnosed in 26.3% patients negative for HCV RNA and 60.0% patients positive for HCV RNA. Decompensated liver cirrhosis was diagnosed in 33.3% HCV RNA-positive patients and none of the HCV RNA-negative patients. The rate of liver cirrhosis was greater for HCV genotype 3a compared with other genotypes. Overall, the current primary HCV RNA genotypes among hemophilia patients co-infected with HIV/HCV are 1a, 1b and 3a. Over 50% of HIV/HCV co-infected hemophilia patients positive for HCV RNA were diagnosed with liver cirrhosis and some were diagnosed with decompensated liver cirrhosis.